Produção e qualidade fisiológica de sementes de feijão-vagem em função das doses de composto orgânico - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Pod beans are a legume of social and agricultural relevance, for being an important source of iron and other nutrients, for being accessible to the entire population and for various preparations for human consumption. Among the possibilities of productive systems we have the organic system which has as main purpose the recycling of nutrients resulting from the creation of animals and human activity, the non-contamination of the environment and the continuous chemical and physical improvement of the soils. Seed quality is of paramount importance to support any production system, with the search for seeds becoming more vigorous with rapid and uniform germination. In addition to the requirement to certify a product as organic, organic seeds must be used. Based on this, the objective of the work was to evaluate the influence of doses of organic compost on the production and physiological quality of the seeds of the bean. The experiment was carried out in the greenhouse at the State University of Goiás, Câmpus Ipameri. The experimental design adopted was completely randomized, with 5 treatments and four replications, the experimental plot was composed by 6 pots of 10 liters, where four plants were cultivated. The treatments were applied 15 days before sowing by applying the doses of organic compost (0, 30, 60, 90 and 120 t ha-1), concomitantly added and incorporated 4 t ha-1 of YOORIN Master® in all pots. The cultivar used was Butter, which has a determined growth habit. The variables analyzed were chlorophyll content, plant height, stem diameter, number of pods per plant, number of seeds per pod, fresh and dry plant mass, productivity, thousand seed mass, germination, first germination count, emergence seedling in sand, seedling emergence speed index in sand, seedling length, seedling dry mass, electrical conductivity, accelerated aging. It was observed that the use of doses of organic compost had a positive influence on plant height, the fresh weight of plants, the number of pods per plant, the number of seeds per pod, seed yeld, seedling length, dry mass seedlings and mass of 1000 seeds. The maximum dose of 120 t ha-1 in the cultivation of pod beans, provided better results for growth, plant weight as well as for production and seed mass, however it was not enough to certify which dose was responsible for the best physiological potential.
Keywords: Phaseolus vulgaris L.; Agricultura orgânica; Húmus; adubação; Phaseolus vulgaris L.; Organic agriculture; Humus; fertilizing; CIENCIAS AGRARIAS